CHI '14 Extended Abstracts on Human Factors in Computing Systems 2014
DOI: 10.1145/2559206.2579422
|View full text |Cite
|
Sign up to set email alerts
|

Exploring tapping with thumb input for flexible tablets

Abstract: Flexible displays offer new interaction techniques, such as bend gestures, but a little work has been done to support touch input, the most common input for handheld displays. In this paper, we explore touch input using the thumb of the holding hand, and compare it for different tapping tasks, between a flexible and a rigid tablet. We present initial design guidelines to use touch input with thumb in flexible devices. Our result suggests that users can perform tapping interaction using thumb input in both rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Wagner et al's results suggest that participants significantly preferred bimanual taps (with the thumb) over other bimanual gestures. Riyadh explored tapping with the thumb of the holding hand on flexible tablets and found that users can efficiently interact with their thumb on both rigid and flexible devices [6]. He identifies a preference for holding the device on the center of the sides or the bottom corners (analogous with BiPad's findings).…”
Section: Thumb Interaction With Touch Devicesmentioning
confidence: 90%
See 2 more Smart Citations
“…Wagner et al's results suggest that participants significantly preferred bimanual taps (with the thumb) over other bimanual gestures. Riyadh explored tapping with the thumb of the holding hand on flexible tablets and found that users can efficiently interact with their thumb on both rigid and flexible devices [6]. He identifies a preference for holding the device on the center of the sides or the bottom corners (analogous with BiPad's findings).…”
Section: Thumb Interaction With Touch Devicesmentioning
confidence: 90%
“…This leverages Riyadh's findings in terms of hold position and touch targets [6]. We chose to use pressure sensors as a quick and inexpensive prototyping material, since flexible transparent touch sensors are currently difficult to find.…”
Section: Prototypesmentioning
confidence: 99%
See 1 more Smart Citation
“…They believe that the flexible film could be used as a lens that, when folded back, could reveal new information, apply photo effects, navigate in z-depth, or be used to create paper-like animation. Md Riyahd looked into tapping interaction done by the thumb of the holding hand of a device (Riyadh, 2014). They compared a rigid device to a flexible device and found that the accuracy of tapping interactions remained mostly constant between devices.…”
Section: Deformation Interactions With Other Inputmentioning
confidence: 99%